Wizje sukcesu edukacyjnego w szkole wyższej. Rozważania w perspektywie paradygmatów edukacyjnych - Sladek, Anna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
This paper presents the description of the vision of educational success in four educational paradigms in higher education. Every paradigm emphasizes different educational aims and values, which are the basis of these aims. The educational process in every paradigm gives students varied possibilities to achieve their own vision of educational success. Some of them have more chance to complete a higher school with a sense of achievement of the success. But for others their own vision of educational success lies outside the school and teachers’ vision of educational success.
Keywords: paradygmaty edukacyjne; sukces edukacyjny; szkoła wyższa